2003
DOI: 10.1097/01.ju.0000066849.32466.2b
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Repeat Percutaneous Epididymal Sperm Aspiration Procedures

Abstract: More than a third of repeat PESA attempts resulted in the presence of motile sperm. Before performing testicular sperm aspiration or extraction in patients who have undergone previous PESA without achieving pregnancy, repeat PESA may be done. Further attempts should be added in the future to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…It has been suggested that the subsequent scarring could impair the efficacy of repeat procedures that are invariably necessary as the chances of sufficient sperm being retrieved for cryopreservation with such aspiration procedures are low. This is confirmed in a recent study that reported motile sperm for ICSI in only 26% of repeat PESA procedures 24 …”
Section: Sperm Retrieval Techniquessupporting
confidence: 79%
“…It has been suggested that the subsequent scarring could impair the efficacy of repeat procedures that are invariably necessary as the chances of sufficient sperm being retrieved for cryopreservation with such aspiration procedures are low. This is confirmed in a recent study that reported motile sperm for ICSI in only 26% of repeat PESA procedures 24 …”
Section: Sperm Retrieval Techniquessupporting
confidence: 79%
“…Optional treatment of these cases is usually using testicular sperm extract (TESE) or donor sperm. The fact is that the parameter of TESE in the oligozoospermia patients without obstructive factor is obviously worse than the ejaculate semen, and immature TESE gametes may cause lower reproductive ability [ 19 , 20 ] and the risks of potential imprinting defects [ 21 23 ]. Utilization of own gametes instead of donors to become a biological parent is always an aspiration for the couple.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted during the last decade has provided growing support to the concept that oxidative stress (OS) is one of the main causes of male infertility. Oxidative stress occurs either as a result of increased levels of reactive oxygen species or insufficient antioxidant capacity (6,7).…”
mentioning
confidence: 99%